2011
DOI: 10.1017/s0021859611000323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of household land management on cropland topsoil organic carbon storage at plot scale in a red earth soil area of South China

Abstract: SUMMARYAn inventory of topsoil soil organic carbon (SOC) content in household farms was performed in a village from a red earth region in Jiangxi Province, China in 2003. In this region, the farmland managed by each household is fragmented, consisting of several plots of land that are not necessarily adjacent to each other. A statistical analysis of SOC variation with land use and household management type, and with crop management practices was conducted. Plot size ranged from 0·007 to 0·630 ha with a mean of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
4
6
0
1
Order By: Relevance
“…Similarly, Tan et al (2008) examined the impact of land fragmentation on the production costs of rice farm in Jiangxi and found an increase in farm size decreased the total production cost. Feng et al (2011) reported that topsoil SOC storage could be higher over 30 % in larger sized farms (>0.7 ha, 10 Chinese mu) than in smaller ones (<0.7 ha) from survey work in a similar region as this study. In a comparable study using questionnaire data, Sefeedpari et al (2013) reported that farms less than 1 ha had a higher total energy input by 17, 21, and 34 % respectively than those of 1-4, 4-10, and >10 ha for rain-fed wheat production from central Iran.…”
Section: Role Of Ch 4 Emissions and N Fertilizer In Carbon Footprint supporting
confidence: 63%
See 1 more Smart Citation
“…Similarly, Tan et al (2008) examined the impact of land fragmentation on the production costs of rice farm in Jiangxi and found an increase in farm size decreased the total production cost. Feng et al (2011) reported that topsoil SOC storage could be higher over 30 % in larger sized farms (>0.7 ha, 10 Chinese mu) than in smaller ones (<0.7 ha) from survey work in a similar region as this study. In a comparable study using questionnaire data, Sefeedpari et al (2013) reported that farms less than 1 ha had a higher total energy input by 17, 21, and 34 % respectively than those of 1-4, 4-10, and >10 ha for rain-fed wheat production from central Iran.…”
Section: Role Of Ch 4 Emissions and N Fertilizer In Carbon Footprint supporting
confidence: 63%
“…However, big scale farms in China with intensive management have been developed in land consolidation programs. Constraints on land resource availability due to fragmented croplands and small household management systems impact on crop production (Tan et al 2008;Feng et al 2011). Schäfer and Blanke (2012) indicated that there were significant differences of CF among the different scales of farm business for pumpkin production.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was also observed in crop production. For example, Feng et al (2011) reported that topsoil SOC storage could be over 30% higher in larger sized farms (>0.7 ha) than in smaller ones (<0.7 ha) from a survey work in a region of China. Sefeedpari et al (2013) also presented that farms less than 1 ha had a higher total energy input by 17, 21 and 34% respectively than those of 1e4 ha, 4e10 ha and >10 ha for rain-fed wheat production from central Iran.…”
Section: Mitigation Strategies Linked To Cf In Livestock and Poultry mentioning
confidence: 99%
“…Their potential impact on SOC had again received much attention for the globe other than China [52]. A pilot study of soil quality and household farming was conducted in a rural area of Jiangxi Province where the local people had been traditionally living on their land [53]. In this case, the topsoil SOC varied widely from 1.7 to 25.2 g kg 1 , depending on the size of total cropland area and the land tenure status.…”
Section: Recent Carbon Stock Dynamics and Sequestrationmentioning
confidence: 99%
“…In addition, land management systems for croplands tend to have an impact on their technological potential. For example, a recent study has shown that significantly higher, by up to one third, SOC sequestration rates in croplands with a bigger plot size and non-leased croplands than those in smaller and sub-contracted or leasing arrangements [53]. Evidently, improving the land tenure system and developing scaled cropland management would be one of the major approaches to working towards enhancing SOC sequestration in China's croplands.…”
Section: Recent Carbon Stock Dynamics and Sequestrationmentioning
confidence: 99%